The prevalence of clinically significant sleep apnoea syndrome in the Netherlands. Issue 8 (1st August 1998) - Neven, A Knuistingh; Middelkoop, H A M; Kemp, B; Kamphuisen, H A C; Springer, M P
Abstract : BACKGROUND: Figures for the prevalence of sleep apnoea syndrome range from 0.3% to 8.5%. These widely ranged estimates are probably due to differences in the definitions used, study designs, and study populations. A study was undertaken to determine the lower limit of the prevalence of clinically significant sleep apnoea syndrome. METHODS: A cross sectional survey by postal questionnaire was carried out in a general practice of a small town in which three doctors serve 93% of its population of 6747 inhabitants of all ages. All men aged 35 and over and women aged 50 and over were invited to fill in a specially designed questionnaire on snoring and sleep. All men and women whose answers suggested the possible occurrence of sleep apnoea were invited to undergo further investigation. Oronasal thermistry was performed in the subjects' homes and the results were scored to provide an apnoea index (AI). Those subjects with an AI of ⩾5 were referred to a sleep laboratory for investigation by polysomnography. RESULTS: Of the 2466 questionnaires issued, 2182 (88.5%) were completed and returned. The occurrence during the previous three months of regular snoring, together with daytime sleepiness and/or partners' observation of interruptions in breathing at night, was reported by 194 subjects (169 men, 25 women). In 173 subjects oronasal thermistry applied in their homes provided satisfactory recordings and, of these, 24 men and one woman had an AI of ⩾5. Analysis of the polysomnographic findings showed that 14 men and one woman met the criteria for sleep apnoea syndrome. Scrutiny of their case records disclosed that in seven men this was clinically significant. CONCLUSIONS: Our findings suggest that the prevalence of clinically significant sleep apnoea syndrome in men aged 35 and over is at least 0.45%. Extrapolation to the population of the Netherlands suggests that at least 16 000 men suffer from sleep apnoea syndrome that should be relieved by medical care. A large proportion of these subjects remains to be diagnosed.